Use of biocides and insect repellents and risk of hypospadias. Issue 3 (1st December 2009) - Dugas, J; Nieuwenhuijsen, M J; Martinez, D; Iszatt, N; Nelson, P; Elliott, P
Abstract : Background: The relationship between the use of biocides and insect repellents and the risk of hypospadias was examined in a large case–control study in the South East of England. Methods: A case–control study was carried out among 471 cases of hypospadias referred to surgeons, and 490 randomly selected population-based controls, born between 1 January 1997 and 30 September 1998. Telephone interviews were conducted between September 2000 and March 2003. The questionnaire included information on demographic, lifestyle and environmental factors, including the use of biocides and insect repellents, during pregnancy. A total biocide score was created from summing positive responses to an eight-item biocide exposure questionnaire. Results: The use of insect repellent (adjusted OR 1.81, 95% CI 1.06 to 3.11) during the first trimester of pregnancy was associated with risk of hypospadias, but none of the biocides, or indicators for them, except for the total biocide score for the highest two exposure categories (score 3: adjusted OR 1.73, 95% CI 1.02 to 2.94; and scores 4 and 5 combined: adjusted OR 2.98, 95% CI 1.01 to 8.78) showed statistically significant associations. Conclusion: The authors found an association between the use of insect repellent and total biocide score and risk of hypospadias. In particular, the use of insect repellent warrants further investigation, specifically in relation to type, content and frequency of use since this information was missing in the current study.